Effect of environmental conditions on morphological variability of leaves and fruits of five populations of Pistacia atlantica Desf. in North Algeria - Nadjat, Taib; Tayeb, Sitayeb (Biodiversity: Research and Conservation, 2020)
Pistacia atlantica has a lot of medical, pharmaceutical and economic benefits, and its variability shows its evolutionary potential. The objective of this study was to investigate morphological and micro-morphological variability of these trees within different ecological regions. This study offers a general description of sites, an analysis of morphological variability of twenty quantitative and qualitative parameters based on the impact of natural and artificial conditions, and leaf anatomical analysis. The results showed that the population exhibited heterogeneity in all parameters of the leaf related to changes in soil, density, climate and slope. Variability in nut size was also demonstrated which was due to the effects of climate, type of soil and topographic factors. The results of electron microscope scanning of leaf anatomy showed the existence of large micro-morphological variability between study sites.